(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2026)
Paddy are a strategic food commodity that plays an important role in national food security. As the main source of carbohydrates, increasing rice production is a priority in the agricultural sector. To date, the main problems encountered in the field are pest and disease attacks, including brown planthoppers (Nilaparvata lugens), rice stem borers (Scirpophaga incertulas), and rice field rats (Rattus argentiventer) as well as several other important diseases in rice plants. This Community Partnership Program (PKM) aims to: (i) improve farmers’ understanding and skills in implementing IPM, (ii) reduce farmers’ dependence on chemical pesticides, (iii) increase the productivity and sustainability of paddy farming businesses. This PKM activity was carried out in Paheleten Village, Kakas District, Minahasa Regency, and the Talun Rekat Group acted as a partner. The activity was carried out in the form of in-room extension. Farmers were introduced to the basic concepts of IPM and pest management strategies that combine various control methods that are mutually compatible and environmentally friendly. To determine farmers’ knowledge of IPM, a pre-test and post-test were conducted. The direct result of this activity is increased capacity of individual farmers, particularly in IPM. Furthermore, changes in social interaction patterns among group members are evident. This phenomenon demonstrates that a participatory approach can strengthen the independence of farmer groups in making decisions based on field evidence. Thus, this PKM activity not only increases individual knowledge but also strengthens farmer group institutions in managing their agricultural ecosystems more wisely. The results of this activity can be published in a National Journal with ISSN, specifically in the Community Service section.